2015
DOI: 10.1002/hep.27962
|View full text |Cite
|
Sign up to set email alerts
|

4′‐modified nucleoside analogs: Potent inhibitors active against entecavir‐resistant hepatitis B virus

Abstract: Certain nucleoside/nucleotide reverse transcriptase (RT) inhibitors (NRTIs) are effective against HIV-1 and HBV. However, both viruses often acquire NRTI resistance, making it crucial to develop more potent agents that offer profound viral suppression. We report here that 4′-C-cyano-2-amino-2′-deoxyadenosine (CAdA) is a novel highly potent inhibitor of both HBV (IC50=0.4 nM) and HIV-1 (IC50=0.4 nM). In contrast, the approved anti-HBV NRTI entecavir (ETV) potently inhibits HBV (IC50=0.7 nM) but is much less act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 35 publications
2
55
1
Order By: Relevance
“…Entecavir is the most potent anti-hepatitis B NRTI drug, and sofosbuvir is the most successful anti-hepatitis C virus nucleotide drug (1)(2)(3)(4)(5). 4′-Ethynyl-2-fluoro-2′-deoxyadenosine (EFdA) extends this concept as an anti-HIV agent.…”
mentioning
confidence: 99%
“…Entecavir is the most potent anti-hepatitis B NRTI drug, and sofosbuvir is the most successful anti-hepatitis C virus nucleotide drug (1)(2)(3)(4)(5). 4′-Ethynyl-2-fluoro-2′-deoxyadenosine (EFdA) extends this concept as an anti-HIV agent.…”
mentioning
confidence: 99%
“…We previously reported that CAdA and CdG highly potently suppressed the replication of a wild-type HBV genotype D (HBV WT D ) in HepG2.2.15 cells. CAdA and CdG also suppressed the production of wild-type HBV genotype Ce (HBV WT Ce ) in HBV WT Ce plasmid-transfected Huh7 cells and potently decreased the HBV WT Ce viremia level in HBV WT Ce -exposed human liver-chimeric mice (19). CAdA and CdG were also potent against a highly ETV-resistant HBV variant containing three critical amino acid substitutions: L180M, S202G, and M204V (HBV L180M/S202G/M204V ) as examined in HBV L180M/S202G/M204V plasmid-transfected Huh7 cells and HBV L180M/S202G/M204Vexposed human liver-chimeric mice.…”
Section: Resultsmentioning
confidence: 99%
“…CAdA and CdG were also potent against a highly ETV-resistant HBV variant containing three critical amino acid substitutions: L180M, S202G, and M204V (HBV L180M/S202G/M204V ) as examined in HBV L180M/S202G/M204V plasmid-transfected Huh7 cells and HBV L180M/S202G/M204Vexposed human liver-chimeric mice. However, both compounds proved to be much more cytotoxic than ETV, and they were dropped from further development (19). Thus, based on the structural findings that we had obtained (19,20), we continued the design and synthesis of approximately 220 novel nucleoside analogs containing a cyano moiety at the 4= position of the ribose and identified CMCdG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations